Analytical modeling of reservoir effect on electromigration in Cu interconnects - Zaporozhets, T. (2012)
Electromigration (EM) in Cu dual-damascene interconnects with extensions (also described as overhangs or reservoirs) ranging from 0 to 120 nm in the upper metal (M2) was investigated by an analytical model considering the work of electron wind and surface/interface energy. It was found that there exists a critical extension length beyond which increasing extension lengths ceases to prolong electromigration lifetimes. The critical extension length is a function of void size and electrical field gradient. The analytical model agrees very well with existing experimental results. Some design guidelines for electromigration-resistant circuits could be generated by the model.